Kepemimpinan Etis, Karakteristik Pekerjaan, dan Kepuasan Kerja Karyawan Maskapai Penerbangan - Cecep Pahrudin; Sandriana Marina; Lira Agusinta (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
This study examined at the effects of ethical leadership, job chracteristics, and individual factors on airline employees’ job satisfaction. It makes use of samples of the airline employees from a Indonesia airline company. From the results of structural equation modelling analysis, ethical leadership and job chracteristics were found positive effect on airline employees’ job satisfaction as well as ethical leadership were found positive effect on airline employees’ job chracteristics. In addition, leaders are also more likely to choose employees who are able to work independently and see the value of their own work and work with an ethical environment.